Genomic Medicine: A Critical Review of its Impact on Diagnosing and Treating Genetic Disorders - Sundaram, Vickram; Rengarajan, Sindhu Kaviya; Manikandan, Sivasubarmanian; Anbalagan, Saravanan; Sivakumar, Vidhya Lakshmi; Packiyam, Thamarai; Chopra, Hitesh (Current Gene Therapy, 2025)
Genomic medicine is revolutionizing genetic disease diagnosis and therapy; has a major impact on clinical practice, particularly in diagnosis and treatment. In addition, next-generation sequencing (NGS) has transformed diagnostics. These advances have made genome profiling cost-effective and fast, helping us find pathogenic variations that cause a variety of genetic illnesses. Given its influence on diagnostic methods, NGS mutation detection accuracy and reliability must be assessed. In therapeutics, genomic medicine has introduced precision methods. CRISPR-Cas9 gene editing, and new RNA-based therapies are being evaluated for the treatment of genetic mutations Pharmacogenomics' capacity to customize medication regimens to genetic profiles, optimizing therapeutic results while minimizing side effects, is also evaluated. Although genetic medicine has transformational promise, its widespread acceptance is difficult. Obtaining widespread acceptance of genetic medicine is difficult because of worries around ethical implications, privacy problems, and the possibility for genetic information to be misused. Ethics and privacy issues surrounding genetic information usage require considerable thought. Genomic data integration into clinical practice requires robust regulatory frameworks. The influence of NGS technology and precision treatments on genetic disease diagnosis and therapy is significant. This review emphasizes the importance of assessing diagnostic tools, comprehending novel therapy modalities, and addressing ethical and regulatory issues to enable responsible and successful clinical integration.
Keywords: genetic disorder